The Bulacan Provincial Library and its community an information needs analysis - Avila, Lenra Machrine E.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
The study aimed to identify the information needs of the residents of Malolos City to assess how the Bulacan Provincial Library meets information needs of its residents. The study also aimed to identify the gaps between, public library standards of the Board for Librarians (BFL), current library collections and services, perceptions of the residents and expectations of the library staff with reference to meeting the stated goals and objectives of the Bulacan Provincial Library.
The study utilized the descriptive research method. The main tool used for data gathering was a survey questionnaire. The respondents were the head librarian of the Bulacan Provincial Library and the residents of Malolos City which were randomly selected at: Bulacan State University; Bulacan Medical Center; Malolos Central Terminal; Puregold Jr. Malolos Branch; and Barasoain Church. The information gathered from the residents and from the head librarian through interview was then analyzed.
The study concluded that while the Bulacan Provincial library strictly follows the standards, there is still a gaps between both parties. The gap originated not from the regular visitors of the library but of those unfamiliar with the existence of the library. While resident visitors were satisfied with the library, more than half of the respondents were still unaware of the library and its location. It is also alarming that almost half of them were convinced that they can obtain the information needs from the internet. With this, the researcher recommends to improve its library marketing in able to help the Bulacan Provincial library accordingly.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information services; Information needs analysis -- Bulacan Provincial Library